DEVELOPING STUDENT COMPETENCIES THROUGH A CREATIVE APPROACH TO TEACHING ELEMENTARY PROGRAMMING (Web of Technology: Multidimensional Research Journal, 2024)
This article presents suggestions and recommendations for teaching students programming languages and forming their programming competence based on the competency approach.